Socio-Demographic Influence and Food Security Against Stunting Events In Medan City - Sitompul, Vetra Sarah; Sudaryati, Etti; Aritonang, Evawany Y. (Green Publisher Indonesia, 2023)
Children's welfare in the health aspect can be seen in the level of growth and development of children. Socio-demographics and family food security are important because they affect the nutritional status of the community. If food security and sociodemographics are lacking, nutritional status will also be lacking and cause a decline in health status. This condition can lead to malnutrition or stunting in the community. This study aims to analyze the influence of socio-demographics and food security on the incidence of stunting in Medan City. This type of research is quantitative observational with a survey research study design using a cross-sectional study design that examines at a certain point in time the entire sample population or predetermined subset. The sample in this study was 266 toddlers from Medan Tuntungan, Medan Maimun, Medan Sunggal, Medan Helvetia and Medan Denai sub-districts. The analytical method used is bivariate analysis using the chi square test and multivariate analysis using logistic regression. The results showed that there was a positive and significant effect of the variables of mother's education, birth spacing and family income on the incidence of stunting in toddlers in Medan City with a p value <0.05. Furthermore, it was found that there was no significant effect of the variable number of children, mother's occupation and family food security on the incidence of stunting in toddlers in Medan City. Mothers should be able to find additional sources of income that can increase family income without neglecting the provision of good parenting for toddlers. This is done to increase the understanding of mothers in providing adequate nutritional intake to children under five